Promoting Effect of Cerium Oxide on the Catalytic Performance of Yttrium Oxide for Oxidative Coupling of Methane - Haneda, Masaaki; Katsuragawa, Yuya; Nakamura, Yuichiro; Towata, Atsuya (Frontiers in Chemistry, 2018)
The promoting effect of CeO2 on the catalytic performance of Y2O3, which is moderately active catalyst, for the oxidative coupling of methane (OCM) reaction was investigated. The addition of CeO2 into Y2O3 by coprecipitation method caused a significant increase in not only CH4 conversion but also C2 (C2H6/C2H4) selectivity in the OCM reaction. C2 yield at 750 C was increased from 5.6% on Y2O3 to 10.2% on 3 mol% CeO2/Y2O3. Further increase in the CeO2 loading caused an increase in non-selective oxidation of CH4 to CO2. A good correlation between the catalytic activity for the OCM reaction and the amount of H2 consumption for the reduction of surface/subsurface oxygen species in the H2-TPR profile was observed, suggesting the possibility that highly dispersed CeO2 particles act as catalytically active sites in the OCM reaction. The 16O/18O isotopic exchange reaction suggested that the beneficial role of CeO2 in the OCM reaction is to promote the formation of active oxygen species via the simple hetero-exchange mechanism, resulting in the promotion of CH4 activation.